Homology Modeling of Alpha-Glucosidase from Candida albicans: Sequence Analysis and Structural Validation Studies in silico - Rashid, Haroon Ur [UNESP]; Bolzani, Vanderlan S. [UNESP]; Khan, Khalid; Dutra, Luiz Antonio [UNESP]; Ahmad, Nasir; Wadood, Abdul (Sociedade Brasileira de Quimica (SBQ), 2023)
The alpha-glucosidase enzyme of Candida albicans plays a vital role in the pathogenesis of candidiasis, a serious fatal disease in immune-compromised patients. The unavailability of the three-dimensional crystallographic structure of this enzyme creates a hindrance in developing novel and potent inhibitors. Here, an attempt has been made to design a stable three-dimensional conformer of alpha-glucosidase through in silico analysis which may be helpful for the designing of effective drugs. For this purpose, the oligo-1-6-glucosidase enzyme is used as a template for homology modeling of the alpha-glucosidase structure by Molecular Operating Environment 2011-12 software. The generated model was validated through ERRAT and Ramachandran tools, whereas its stability was studied through the molecular dynamics simulation technique. The obtained results indicate that model of alpha-glucosidase has stable secondary and tertiary arrangements. This finding may spur new directions for the rational designing and development of new antifungal inhibitors. Nevertheless, additional experimental investigations and validation are needed to confirm the in silico results of this study.
Keywords: alpha-glucosidase; candidiasis; homology modeling; simulations